Skeletal Muscle Contractile Function in Heart Failure With Reduced Ejection Fraction—A Focus on Nitric Oxide - Park, Lauren K.; Coggan, Andrew R.; Peterson, Linda R. (Frontiers in Physiology, 2022)
Despite advances over the past few decades, heart failure with reduced ejection fraction (HFrEF) remains not only a mortal but a disabling disease. Indeed, the New York Heart Association classification of HFrEF severity is based on how much exercise a patient can perform. Moreover, exercise capacity – both aerobic exercise performance and muscle power – are intimately linked with survival in patients with HFrEF. This review will highlight the pathologic changes in skeletal muscle in HFrEF that are related to impaired exercise performance. Next, it will discuss the key role that impaired nitric oxide (NO) bioavailability plays in HFrEF skeletal muscle pathology. And lastly, it will discuss intriguing new data suggesting that the inorganic nitrate ‘enterosalivary pathway’ may be leveraged to increase NO bioavailability via ingestion of inorganic nitrate. This ingestion of inorganic nitrate has several advantages over organic nitrate (e.g., nitroglycerin) and the endogenous nitric oxide synthase pathway. Moreover, inorganic nitrate has been shown to improve exercise performance: both muscle power and aerobic capacity, in some recent small but well-controlled, cross-over studies in patients with HFrEF. Given the critical importance of better exercise performance for the amelioration of disability as well as its links with improved outcomes in patients with HFrEF, further studies of inorganic nitrate as a potential novel treatment is critical.